The Association between Patient-Related Factors with Seriousness of Adverse Drug - Leeyutthanont, Taweechai; Yothapitak, Jantima (Region 11 Medical Journal, 2023)
Background: Adverse drug reactions (ADRs) are those that are unintended and harmful to humans when used in normal doses. The severity of ADRs results in hospitalization and lengthening of treatment or may be disabled or even die. Objectives: To study the relationship between patient-related factors and the severity of ADRs. Method: It is a retrospective study. Analyze patient-related factors such as gender, age, history of drug/food/chemical allergies. Descriptive statistics were used for the frequency, percentage, and the relationship between the factors related to the patients studied and the severity of the occurrence of ADRs using chi-square statistics. Results: The results showed that 52.50% were female and 47.50% were male. The age group with the highest ADRs was 51-60 years old 18.20%. Patients had a history of drug/food/chemical allergy 19.90% and no history 80.10%. The drug groups that cause the most ADRs are: Antibacterial drugs 42.10% and other drugs 57.90%. Regarding the seriousness of symptoms, ADRs were found to be serious 22.50% with no seriousness 77.50%. There was a statistically significant difference between the drug group and the ADRs severity (p=0.037 and p<0.001, respectively). Conclusion: The severity of adverse drug reactions was related to patient age and drug group.